2018
DOI: 10.1080/19390211.2018.1429516
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Leaf Ethanolic Extract Etlingera hemisphaerica Blume Against Mercuric Chloride Toxicity in Blood of Mice

Abstract: This research was intended to investigate the protective effect of leaf ethanolic extract Etlingera hemisphaerica Blume (LE3H) against mercuric chloride (HgCl) toxicity in blood of mice (Mus musculus). The experimental animals, 95 male M. musculus, received drink and food ad libitum. Three materials were tested: LE3H (0.13, 0.26, 0.39 mg/g body weight [bw]) was administered by gavage; HgCl (5 mg/kg bw) was administrated by gavage or intraperitoneal injection; and Imunos (the nutritional supplement to stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
0
12
0
2
Order By: Relevance
“…Based on the results of previous studies [ 16 , 17 ], this study used a single dose of E . hemisphaerica leaf ethanol extract (LE3H), namely 0.39 mg/g bw [ 15 ]. Hg in the form of HgCl 2 was obtained from Merck (Germany; Product No.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the results of previous studies [ 16 , 17 ], this study used a single dose of E . hemisphaerica leaf ethanol extract (LE3H), namely 0.39 mg/g bw [ 15 ]. Hg in the form of HgCl 2 was obtained from Merck (Germany; Product No.…”
Section: Methodsmentioning
confidence: 99%
“…LE3H shows potential protective effects against HgCl 2 toxicity in blood of mice. Therefore, dietary supplements of LE3H may be useful for protecting persons who are exposed to HgCl 2 [16]. Our previous study indicated that LE3H decreased malformed living fetus as teratogenicity effects of HgCl 2 in mice [17].…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations